Measurements of Higgs boson production and couplings in the four-lepton channel in pp collisions at center-of-mass energies of 7 and 8 TeV with the ATLAS detector - Onofre, A. (2015)
The final ATLAS Run 1 measurements of Higgs boson production and couplings in the decay channel H→ZZ∗→ℓ+ℓ−ℓ′+ℓ′−, where ℓ,ℓ′=e or μ, are presented. These measurements were performed using pp collision data corresponding to integrated luminosities of 4.5 fb−1 and 20.3 fb−1 at center-of-mass energies of 7 TeV and 8 TeV, respectively, recorded with the ATLAS detector at the LHC. The H→ZZ∗→4ℓ signal is observed with a significance of 8.1 standard deviations at 125.36 GeV, the combined ATLAS measurement of the Higgs boson mass from the H→γγ and H→ZZ∗→4ℓ channels. The production rate relative to the Standard Model expectation, the signal strength, is measured in four different production categories in the H→ZZ∗→4ℓ channel. The measured signal strength, at this mass, and with all categories combined, is 1.44 +0.40−0.33. The signal strength for Higgs boson production in gluon fusion or in association with tt¯ or bb¯ pairs is found to be 1.7 +0.5−0.4, while the signal strength for vector-boson fusion combined with WH/ZH associated production is found to be 0.3 +1.6−0.9.